Ranakinestatin-PPF from the Skin Secretion of the Fukien Gold-Striped Pond Frog, Pelophylax plancyi fukienensis: A Prototype of a Novel Class of Bradykinin B2 Receptor Antagonist Peptide from Ranid Frogs - Jie Ma; Yu Luo; Lilin Ge; Lei Wang; Mei Zhou; Yingqi Zhang; Jinao Duan; Tianbao Chen; Chris Shaw (The Scientific World Journal)
The defensive skin secretions of many amphibians are a rich source of bradykinins and bradykinin-related peptides (BRPs). Members of this peptide group are also common components of reptile and arthropod venoms due to their multiple biological functions that include induction of pain, effects on many smooth muscle types, and lowering systemic blood pressure. While most BRPs are bradykinin receptor agonists, some have curiously been found to be exquisite antagonists, such as the maximakinin gene-related peptide, kinestatin—a specific bradykinin B2-receptor antagonist from the skin of the giant fire-bellied toad, Bombina maxima. Here, we describe the identification, structural and functional characterization of a heptadecapeptide (DYTIRTRLHQGLSRKIV), named ranakinestatin-PPF, from the skin of the Chinese ranid frog, Pelophylax plancyi fukienensis, representing a prototype of a novel class of bradykinin B2-receptor specific antagonist. Using a preconstricted preparation of rat tail arterial smooth muscle, a single dose of 10−6 M of the peptide effectively inhibited the dose-dependent relaxation effect of bradykinin between 10−11 M and 10−5 M and subsequently, this effect was pharmacologically-characterized using specific bradykinin B1- (desArg-HOE140) and B2-receptor (HOE140) antagonists; the data from which demonstrated that the antagonism of the novel peptide was mediated through B2-receptors. Ranakinestatin—PPF—thus represents a prototype of an amphibian skin peptide family that functions as a bradykinin B2-receptor antagonist herein demonstrated using mammalian vascular smooth muscle.